PERHITUNGAN LEBAR RETAK PADA BETON PRATEKAN PARSIAL DENGAN UNIFIED APPROACH - Gideon Hadi Kusuma (Institute of Research and Community Outreach - Petra Christian University, 2000)
In partially prestressed concrete, crack width is rarely calculated. The crack width was controlled only by limiting the steel stress. This paper introduced crack width calculations which has been developed in America (ACI). The calculations show that factor influencing crack width is not only the steel stresses, but there are some other variables.